Urban Water Resilience: Strategies and Adaptation to Climate Change - Corrêa, Thais Helena Prado; Teixeira, Bernardo Arantes do Nascimento (National Journal of City Management, 2024)
The term Resilience is present in both academia and management; however, Urban Water Resilience (UWR) is still a term that has been scarcely studied, addressed, systematized, and applied in research related to water resources management. The present work was motivated by the need to obtain interpretative data for the UWR, considering its potential and importance regarding the construction of Resilience in the face of climate change. The objective is to propose guidelines and strategies to incorporate UWR in municipalities based on the use of indicators. To this end, the researchers initially sought the direct or indirect presence of UWR in Municipal Plans of Brazilian cities. In the next stage, Urban Water Systems were analyzed based on the Components and Variables related to UWR and Indicators associated with the systematized Variables were suggested, the aforementioned having being used in the proposed method for incorporating UWR. The systematization carried out resulted in fifteen Components and thirty-nine Variables for which fifty-three Indicators were proposed that allow monitoring of UWR. The proposed methodology will enable cities to evaluate the present and build the future by becoming water-safe cities.